ANALISIS PENGALAMAN TAMU DALAM MENIKMATI PELAYANAN DI KINGS HOTEL BATAM - Veronika; Zahara Fatimah; Arina Luthfini Lubis; Yudha Wardani (Universitas Pendidikan Ganesha, 2025)
This study aims to analyze guest experiences at King's Hotel Batam as a basis for improving service quality in the increasingly competitive hospitality industry. The main issues identified are inconsistencies in the implementation of service standards and the gap between guest expectations and actual experiences. The study used a descriptive qualitative approach through in-depth interviews, direct observation, and documentation, including online guest reviews. The results indicate that staff unfriendliness, slow response times, and non-compliance with cleanliness standards are the main factors that reduce guest satisfaction. The findings also reveal differences in service quality between departments. The novelty of the study lies in the integration of field data and digital reviews to identify service gaps more comprehensively. Implications of the study emphasize the need to strengthen service training, align operational standards, and continuously improve quality oversight.